Leo Tolstoy and the Canadian Doukhobors : a study in historic relationships - Donskov, Andrew, 1939- (University of Ottawa Press, 2019)
"Following the completion of his major novels War and Peace and Anna Karenina, Russian writer Leo Tolstoy experienced a spiritual crisis that led him to denounce the privileges of his social class and its attendant material wealth and embrace the simple rural life of the peasantry. In the persecuted Russian Doukhobor sect, who also rejected militarism and church ritual in favour of finding God in their hearts, he saw a prime example of how it was possible to live his new-found pacifist ideals in everyday life. He was so taken with their lifestyle, calling the Doukhobors "people of the 25th century," that, in 1898, he decided to help finance their mass emigration to Canada, away from the persecutions of the Russian church and state. Donskov's expanded study presents an outline of Doukhobor history and beliefs, their harmony with Tolstoy's lifelong aim of "unity of people", and the portrayal of Doukhobors in Tolstoy's writings. This edition features Tolstoy's complete correspondence with Doukhobor leader Pëtr Vasil'evich Verigin. Three guest essays by prominent Canadian Doukhobors are also included. Supported by a considerable array of source materials, Donskov's monograph will be of relevance to anyone interested in religious, philosophical, sociological, pacifist, historical, or literary studies."--